LEGAL PROTECTION FOR LAND RIGHTS HOLDERS IN CASES OF MULTIPLE CERTIFICATES - Anggreyni Simbolon, Ayu Anggi (Communale Journal, 2024)
Land disputes have become a complex and very frequent problem. Various factors, including multiple certificates, can cause land disputes. This research uses normative methods to approach legal norms and relevant legal substance. Enacted in 1960, the UUPA is Indonesia’s primary legal basis governing land rights. The results show that although there are regulations governing land registration and owners’ rights, the legal protection provided to holders of property rights certificates still needs to be improved. Title certificates, which are supposed to be strong evidence, often do not give the expected legal certainty, especially when disputes arise. Land rights holders are expected to receive strong legal protection. The research identified that the community’s lack of understanding of their rights and the applicable legal procedures exacerbated the situation. The research also emphasizes the need for reforms in the land law system, including increased socialization of land rights to the public and improvements in land registration procedures.